Em Roma Sê Romano? Sobre-qualificação na emigração portuguesa - Candeias, Pedro (2024)
The integration of emigrants into the labor market has effects on the person's migration trajectory and their interaction with the host society. It is often overcome by difficulties in adjusting human capital and professional skills to the needs of the labor market. Qualified migration illustrates with acuity the heterogeneity of these processes. The employability of qualified emigration is not uniform. Some emigrants, despite having a higher level of qualification, may find themselves working in unskilled professions – a situation of over-qualification. Based on two studies on Portuguese emigration, over-qualification rates were found in the order of 18.1% and 16.9%. Negative consequences of this over-qualification were identified: dissatisfaction with work and low wages. Factors associated with this over-qualification were also identified: young age, social and human sciences training, and residence in classic Portuguese emigration countries with a high proportion of low-skilled emigration.